Power optimisation for wearable heart rate measurement device with wireless charging. (19th May 2017) - Kiruthiga, G.; Sharmila, A.; Mahalakshmi, P.; Muruganandam, M.
Abstract: Continuous measurement of heart rate is necessary for monitoring the patients with heart ailments. A wearable which continuously measures heart rate of an individual by a method called reflectance-based photoplethysmography (PPG) computes the heart rate of an individual according to the volumetric changes in blood flowing through the body is developed. In order to make the device more compact as well as with IP67 and IP68 standard, wireless charging technique is employed because it helps to get rid of wires while charging. Following the Qi standard for designing wireless power receiver circuits makes the device interoperable and work with greater efficiency with reduced losses. Impedance matching and designing the circuit to operate under resonance condition increases coupling efficiency in case of inductive coupling.